Emergency hospitalization caused by non-COVID-19 respiratory diseases before and during the COVID-19 pandemic: A retrospective observational cohort study - Liu, Qi; Lin, Bingcao; Zhu, Changju; Hu, Jianping (Frontiers in Medicine, 2022)
Background: The coronavirus disease 2019 (COVID-19) pandemic as well as the subsequent prevention and control measures is like a quasi-experiment intervention that might have changed the features of emergency hospitalizations. Mortality is high in patient hospitalization due to emergency respiratory diseases (ERD). Therefore, we compared the characteristics of these patients before and during the pandemic. Exploring this issue might contribute to decision-making of emergency management when most of the resources and attention has been devoted to combat COVID-19 . Methods: This study was a retrospective observational cohort study. All emergency hospitalizations due to ERD from January 1, 2019 to December 31, 2020 in a tertiary hospital in China were included. Data including patients’ age, sex, and clinical outcomes were extracted. Air quality was collected from the official online platform. Clinical characteristics were compared and odds ratios were calculated. Results: The ERD hospitalization rate was lower in 2020 than in 2019 ( 6.4% vs. 4.3%, χ2=55.449, P=0.000) with a 50.65% reduction; however, the patients were older in 2020 than in 2019 (P=0.000) with a higher proportion of admission to the intensive care unit (ICU) ( 46% vs. 33.5%, χ2=20.423, P=0.000) and a longer ICU stay (P=0.000). The overall intubation rate, hospital mortality, and rate of discharge due to ineffective treatment in 2020 were higher than those in 2019 (15.6% vs. 8%, χ2=18.578, P=0.000; 4.2% vs. 1.1%, χ2=4.122, P=0.000; 5.5% vs. 2.4%, χ2 =8.93, P=0.000, respectively). The logistic regression analysis indicated hospitalizations due to ERD were mainly associated with PM2.5 and sulfur dioxide on the day, and on the 4th and 5th days before admission (P=0.034 and 0.020, 0.021 and 0.000, 0.028 and 0.027, respectively) in 2019. However, in 2020, the relationship between parameters of air quality and hospitalization changed. Conclusion: The COVID-19 pandemic has changed the characteristics of emergency hospitalization due to ERD with a larger proportion of severe patients and poorer prognosis. The effect of air quality on emergencies were weakened. During the COVID-19 pandemic, it is necessary to pay more attention to the non-COVID-19 emergency patients.